Croton condorensis: an enigmatic new species of Euphorbiaceae from southern Ecuador - Riina, Ricarda; Vigo, Marco A.; Cerón, Carlos E. (Phytotaxa, 2014)
Croton condorensis (Euphorbiaceae), a new species from the Cordillera del Cóndor in southern Ecuador, is here described and illustrated. The new species occurs in sclerophyllous vegetation on sandstone substrate. A detailed examination of its morphology indicates that the species has some characters in common with Croton sect. Cyclostigma, but it also differs from that section in several other key characters. Given its restricted geographic distribution, the particular substrate where it grows, and its unusual morphology, we hypothesize that Croton condorensis might represent a previously unsampled clade of the Croton phylogeny. Se describe e ilustra Croton condorensis (Euphorbiaceae), una nueva especie de la Cordillera del Cóndor en el sur de Ecuador. Esta especie se encuentra en vegetación esclerófila sobre substrato de arenisca. Una examinación detallada de su morfología indica que la especie comparte algunos caracteres morfológicos con miembros de Croton sect. Cyclostigma, pero también posee caracteres clave que no son compatibles con la morfología de dicha sección. Dada su restringida distribución geográfica, el particular substrato en el que crece, y la falta de afinidades morfológicas evidentes con alguna de las secciones de Croton, planteamos la hipótesis de que Croton condorensis podría representar un clado de la filogenia del género aún no muestreado.